Patient Satisfaction on Discharge Planning Implementation - Baker, Marini Stefani; Hidayati, Laily; Kurnia, Iqlima Dwi (Fundamental and Management Nursing Journal, 2019)
Introduction: Patient satisfaction is one of health services indicator. Discharge planning is an important nursing process since a patient come into the ward till after returning from the hospital. This study aimed to analyze the correlation between discharge planning service with patient satisfaction.Method: The design of this study was cross-sectional. The number of sample was 111 respondents. The independent variables wasdischarge planning implementation. The dependent variable was patient satisfaction. Data were collected using questionnaires and analysis with spearman rho with significancy value is <0,01.Result: The result of the analysis according to Spearman Rho test revealed p = 0,001. This suggest that there was correlation between discharge planning service with patient satisfaction.Conclussion: There was a positive correlation between discharge planning service with patient satisfaction. It means that the better discharge planning service the higher patient satisfaction.